WHEN CORPORATE CULTURE CAN BE A PROBLEM: SYMPTOMS AND CAUSES OF «TOXICITY» - V. Konovalova (Publishing House of the State University of Management, 2019)
The issues of a «toxic» corporate culture, having a negative impact on interpersonal relations, the working atmosphere in a team, the involvement and loyalty of personnel, have been considered. On the basis of theoretical and empirical studies of foreign and Russian scientists, the main manifestations of a «toxic» culture have been summarized. The behavioral attributes and main behavioral patterns of managers, determining the formation of a «toxic» culture, have been highlighted. The methods, aimed at changing both the working environment as a whole, and interaction with «toxic» managers have been proposed.